Ökologische Untersuchungen an Aphiden. II. Über die Fortpflanzungspotenz von Myzus persicae (Sulzer) und Aphis nasturtii (Kaltenbach) auf Kartoffeln (Homoptera: Aphididae). - Neitzel, K.; Raeuber, A. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The propagative power of Myzus persicae (Sulzer) and Aphis nasturtii (Kaltenbach) on potatoes was tested with constant temperatures of 20, 23 and 25 degrees and changing temperatures of 20/30, 20/33, 20/35 degrees in temperature-keeping cabins. The high temperatures were used for three hours a day (from 11 a. m. to 2 p. m.). The evaluation followed the population analysis according to Birch (1948). Aphis nasturtii had the highest rate of increase at changing temperatures of 20/30 and 20/33 degrees (k = 0.33). It reacts promptly to changes of temperature and may be called heat-loving but temperature-sensitive. Myzus persicae tolerates temperatures better than Aphis nasturtii. The potato was a better host for Aphis nasturtii than for Myzus persicae. To facilitate international comparisons ot the results of such tests, they should be based on a suitable population analysis. For virginoparous aphids the determination of the growth factor "k" (or "r" according to Birch 1948) is recommended.